Contribution to the study of the physiology of the Andes - The blood pressure in men at sea level and in the Andean highlands - Torres R., Hernán (1937)
With this work I wanted to contribute - to the modest contingent of my willingness - to study a problem in reaching implications: the physiology of the Andes that has been raised and addressed in many respects by competent national researchers